THE INFLUENCE OF PRODUCTS AND PROMOTIONS ON CUSTOMERS' DECISIONS TO SELECT PRODUCTS AT PT. PRUDENTIAL LIFE ASSURANCE SYARIAH IN THE SUNGAI PENUH CITY - Putra, Mhd Aldino; Sarmigi, Elex (Institut Agama Islam Negeri Kerinci, 2024)
This research aims to determine whether products and promotions influence customers' decisions to use Sharia insurance products. The location of this research is at PT. Prudential Assurance Sungai Penuh City. Data collection techniques in this research are observation, questionnaires and documentation. Meanwhile, the data analysis techniques in this research are questionnaire instrument analysis (validity and reliability), normality test, multicollinearity test, multiple linear regression, coefficient of determination test, and hypothesis testing. The subjects in this research were agents and customers of Prudential Life Assurance insurance products. The population in this study was 217 customers, while the sample was 90 customers using education insurance products in 2023. The research results prove that product variables partially significantly affect the public interest in the Prudential Life Assurance insurance product in Sungai Penuh City. Partially, the product promotion variable only significantly affects the public interest in PT. Prudential Life Assurance insurance in Sungai Penuh City. In simultaneous testing, product and promotional variables significantly affect public interest in Prudential Life Assurance insurance in Sungai Penuh City.